2020
DOI: 10.1063/5.0005189
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on transition structures of oblique detonations with expansion wave from finite-length cowl

Abstract: The oblique detonation wave (ODW) triggered by a semi-infinite cowl or wedge has been widely studied, but the effects of finite-length cowls require further clarification to enhance their applicability. Based on two-dimensional inviscid Euler equations and a two-step induction–reaction model, two structures with smooth and abrupt transitions are simulated, and their interactions with the cowl-induced expansion wave are investigated. The expansion waves located downstream and far away from the initiation zone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(18 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…There are two approaches in research quantitative and qualitative. Becker, et al [111] found that the quantitative approach places emphasis on quantifying the study and uses quantitative analysis, i.e., analyzing data with a deductive approach [112]. Based on previous approaches, the current research used a quantitative approach because this approach is considered to be better when testing the hypothesis, based on the previous theory.…”
Section: Methodsmentioning
confidence: 99%
“…There are two approaches in research quantitative and qualitative. Becker, et al [111] found that the quantitative approach places emphasis on quantifying the study and uses quantitative analysis, i.e., analyzing data with a deductive approach [112]. Based on previous approaches, the current research used a quantitative approach because this approach is considered to be better when testing the hypothesis, based on the previous theory.…”
Section: Methodsmentioning
confidence: 99%
“…Continuous reflection will be observed up to the motor exit. Then to avoid the reflection of the shock wave, the central body of the air intake must be placed according to (21). Knowing that (k=1, φ=ψ, ω=2, P=P 2 ) for the dihedral and (k=2, φ=θ C , ω=π, P=P C ) for the cone.…”
Section: Applicationsmentioning
confidence: 99%
“…The values of P/P 02 and P 02 /P 01 in (21) are respectively given by (18) and 14respectively when T=T 2 , ρ=ρ 2 and P=P 2 , ρ 0 =ρ 02 and P=P 02 for the dihedron, and when T=T C , ρ=ρ C and P=P C , ρ 0 =ρ 02 for the cone. While φ and P 0 are among the data of our study.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis results demonstrated that the use of a hybrid NF of copper and alumina in water dramatically dropped the temperature of the H/S in comparison with applying other NFs. The results of studies on the channels and pipes revealed that the use of wavy walls instead of a flat wall improves heat transfer [34][35][36][37][38]. In one of these articles, Vanaki et al [38] studied the impact of wavy walls on a macro-sized channel.…”
Section: Introductionmentioning
confidence: 99%